2016
DOI: 10.3311/ppee.9706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bismuth and Silver on the Corrosion Behavior of Lead-free Solders in 3.5 wt% NaCl Solution

Abstract: IntroductionOne of the key reliability issues of the electronics technology is carry about the solder joints testing. Usually, the different failures can lead back to the not adequate physical properties (e.g. wetting behaviour, mechanical strength, etc.) of the solder alloy and/or the not adequate applied technological processes (e.g. reflow temperature profile), which have to be improved. This challenge was updated in 2006, with the introduction of lead-free solder alloys governed by the RoHS directive of EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The plots showed that the samples had a capacitive response in a medium frequency range and a resistive response at higher frequencies. The phase angle shift of − 55 • shows the semi-capacitive response due to the heterogeneity of the electrode surface [14]. The obtained results agree with the reported data by Rosalbino et al [3].…”
Section: Potentiostatic Analysissupporting
confidence: 91%
“…The plots showed that the samples had a capacitive response in a medium frequency range and a resistive response at higher frequencies. The phase angle shift of − 55 • shows the semi-capacitive response due to the heterogeneity of the electrode surface [14]. The obtained results agree with the reported data by Rosalbino et al [3].…”
Section: Potentiostatic Analysissupporting
confidence: 91%
“…[6]. Other researches tried to improve the mechanical properties of the SAC alloy with further alloying of Bi and Mn in a higher amount between 0.1-1 wt% [7,8]. Lin et al [9] reached significant mechanical improvement during drop tests in the case of low Ag content Sn-l.0Ag-0.5Cu alloys doped with Mn and Ti (0.15 and 0.5wt%).…”
Section: Introductionmentioning
confidence: 99%
“…While mechanical and physical properties of these new alloys are always evaluated, the same cannot be said for their corrosion behaviour. Although numerous attempts have been conducted to investigate the corrosion behaviour of lead-free solder alloys [29][30][31][32][33][34][35][36][37][38], there is still little information regarding the galvanic corrosion of solder alloys in contact to Cu or Ni substrates; in fact, only a few studies have been reported to date [39,40].…”
Section: Introductionmentioning
confidence: 99%